Analisis Semiotika Roland Barthes terhadap Representasi Diskriminasi Gender Perempuan dalam Film A Normal Woman - Exga Soleha; Yudha Wirawanda (Universitas Islam Tribakti Lirboyo Kediri, 2026)
The practice of discrimination against women is constructed through film screenings and reinforced by societal myths. Gender inequality causes women to experience various disadvantages, making gender discrimination a significant research concern. This phenomenon is represented in the film A Normal Woman, which addresses gender discrimination against women in the modern era. This study aims to gain a deep understanding of how gender discrimination against women is represented through signs that appear in film scenes using Roland Barthes' semiotic analysis. The method used is qualitative descriptive to obtain knowledge related to meanings in the form of connotation, denotation, and myth. The critical paradigm is used to explore and critique societal inequalities and to uncover injustices arising from power relations. Analysis is conducted by identifying visual and verbal signs in selected scenes, describing their denotative meanings (literal), interpreting connotations (socio-cultural meanings), and revealing myths (naturalized patriarchal ideology). The results reveal that the film constructs the myth of